Sustainability and Ethics in Information Systems - Yuniana Cahyaningrum (Ali Institute or Research and Publication, 2025)
In the ever-evolving digital era, the role of information systems (IS) is not only limited to improving business efficiency, but also to contributing to sustainability and social ethics. This study explores the integration of sustainability and ethics concepts in the development and implementation of information systems. With increasing concerns about the environmental impact of information and communication technologies, as well as ethical issues related to data privacy, algorithmic bias, and cybersecurity, it is important for developers and stakeholders to consider these aspects at every stage of the information system life cycle. This study analyzes the approaches taken by organizations in integrating sustainability and ethics principles into their IS strategies, and evaluates their impact on organizational sustainability and social responsibility. The results show that the adoption of ethical and sustainable IS not only improves the company's reputation but also provides added value through operational efficiency and risk reduction. Thus, the implementation of sustainable and ethical IS practices is key to creating long-term competitive advantage and maintaining a balance between technological advancement and social responsibility. Implementing ethical and sustainable information systems not only provides conceptual benefits such as transparency, privacy protection, and fairness, but also strategic benefits such as positive reputation, cost efficiency, and regulatory compliance. Conversely, not using the right methodology in developing information systems can result in a lack of standardization, project management errors, and significant security risks. Therefore, it is important for organizations to implement ethical, sustainable systems that are supported by structured methodologies.